School climate at a private educational institution in San Juan de Lurigancho - Saguma Huamaní, Yuriko Flor de Lirio (2023)
The school climate is based on the perceptions of the members of the educational community about the environment in which they interact. In this sense, the present research aims to analyze how the types of school climate are presented during the return to attendance in a private educational institution in San Juan de Lurigancho. The collection of information was carried out through the application of semi-structured interviews directed to teachers of said institution, based on the category of types of climates. As conclusions, some characteristics were found that describe the school climate in the institution. Likewise, it was identified that there is a positive type of climate in the institution in which a good working environment is promoted. Finally, certain aspects emerge that could lead to possible difficulties in the interaction among the members of the community.